2024
DOI: 10.1038/s41557-023-01428-2
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal editing of pyridines through atom-pair swap from CN to CC

Qiang Cheng,
Debkanta Bhattacharya,
Malte Haring
et al.

Abstract: Skeletal editing is a straightforward synthetic strategy for precise substitution or rearrangement of atoms in core ring structures of complex molecules; it enables quick diversification of compounds that is not possible by applying peripheral editing strategies. Previously reported skeletal editing of common arenes mainly relies on carbene- or nitrene-type insertion reactions or rearrangements. Although powerful, efficient and applicable to late-stage heteroarene core structure modification, these strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The presence of a 15 N nucleus was also observed in the corresponding 1 H and 13 C­{ 1 H} NMR spectra given that several signals appeared as 15 N-coupled doublets as comprehensively summarized in Figure . Mass spectrometric measurements further confirmed that the O atom within the starting material was replaced by an N atom via a skeletal editing process, whichin the present caseis referred to as O-for-N swapping reaction …”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The presence of a 15 N nucleus was also observed in the corresponding 1 H and 13 C­{ 1 H} NMR spectra given that several signals appeared as 15 N-coupled doublets as comprehensively summarized in Figure . Mass spectrometric measurements further confirmed that the O atom within the starting material was replaced by an N atom via a skeletal editing process, whichin the present caseis referred to as O-for-N swapping reaction …”
mentioning
confidence: 65%
“…In conclusion, collidine was prepared from N 2 via a tungsten nitride, which was shown to undergo an O-for-N swapping reaction upon treatment with 2,4,6-trimethylpyrylium triflate. Given that similar atom swapping reactions are scarce, the reaction sequence reported herein is considered particularly relevant, not only in the context of N 2 functionalization, but also in the context of skeletal editinga currently emerging field.…”
mentioning
confidence: 99%
“…Possible reaction mechanisms to form the indolizine and 1,2-dihydropyrimidine products are proposed. Scheme 2A outlines a skeletal editing [9,36] N-deletion mechanism for the formation of indolizine products. Based on our isolation of the cyclobutene intermediate, we propose a stepwise 1,3-dipolar cycloaddition, followed by the addition of a second equivalent of alkyne to form the fused ring system 6 a.…”
Section: Resultsmentioning
confidence: 99%
“…After examining the scope of this transformation, we recognized that the use of more complex sulfoxides could selectively introduce substituents at the newly introduced atom, thereby formally accomplishing an atom-swap/ ipso -functionalization. This type of tandem transformation has been described but is still underexplored. , Although attempts to use simple phenyl alkyl sulfoxides failed to furnish the desired benzene derivatives, possibly due to a deleterious steric effect that prevents ring closure, we found that symmetrical dialkyl sulfoxides can undergo the desired transformation (Scheme A). Linear alkyl groups were introduced to both pyridine and quinoline N -oxide substrates in preparatively useful yields ( 36 – 43 ).…”
mentioning
confidence: 87%
“…There has been a substantial body of research directed toward selective peripheral functionalization of pyridines (e.g., metalations, C–H functionalizations, etc. ). , However, few reports demonstrate the transformation of pyridine scaffolds into other classes of aromatic compounds by ring atom substitution . In considering how this ring atom swap might be achieved, we drew inspiration from the Zincke aldehyde reaction wherein a nucleophilic addition to an activated pyridine ring is attended by ring-opening to a functionalized unsaturated iminium ion. , Morofuji and Kano recently reported a three-step protocol enabling the conversion of pyridines to functionalized benzene derivatives by reacting Zincke intermediates with carbon-based nucleophiles (Figure C) …”
mentioning
confidence: 99%